A solution to unit commitment problem for small island grid with intermittent wind power supply - Jalandoni, Jenny I. (2002)
It is difficult to operate s system economically if the power supply and load demand are varying, one of which is a Small Island Grid with intermittent wind power supply. This problem combined with physical and operating constraints is a Unit Commitment problem. A method using Autoregressive Modeling, Combinatorial Analysis, Lambda Iteration, Monte Carlo technique, and Dynamic programming was developed to solve the Unit Commitment problem of a small island grid with intermittent wind power supply. The island grid power supply is composed of a Diesel units and Wind Energy Converters (WECs) only. Several technical constraints were applied; the significant among thm were capacity, diesel minimum loading, wind penetration factor, and hardware availability. The method dividesthe total simulation period into time intervals. And for every time interval, it predicts the wind power generation, evaluates the availability of the units (due to preventive maintenance and random breakdown), uses dynamic programming to determine the Diesel unit commitment, determines the optimum WECs combination using Combinatorial analysis, and economically dispatches the Diesel plant load using Lambda iteration method. The result of this research is a realistic algorithm, that can determine in advance what WECs and Diesel units would be operating economically in a certain time but satisfying physical and operating constraints. The proposed algorithm was applied to the main island of Palawan province as a case study.